In Vitro Assessment of Pharmaceutical Equivalence of Different Brands of Metformin Hydrochloride Tablets Available in Tertiary Care Hospital in Kathmandu - Timsina, Sakchhyam; Adhikari, Rojina; Prasad, Pravin; Thapaliya, Shristee; Budthapa, Arjun; Sah, Shiv Kumar; Joshi, Mahesh Kumar; Pandeya, Shiva (Journal of Nepal Chemical Society, 2026)
Diabetes mellitus remains a worldwide health burden, associated with a significant co-morbidity, including heart disease, nerve damage, kidney failure, vision loss, and diminished quality of life. Ensuring therapeutic quality of the drugs is vital to safeguard the treatment efficacy, patient safety, and public health outcomes. Therefore, the aim of the study was to establish the pharmaceutical equivalence of various brands of metformin hydrochloride available in tertiary care hospital in Kathmandu. In this study a systematic quality assessment of weight variation, friability, assay, and related substance impurities were evaluated as per the Indian pharmacopeia (IP 2022). The weight variation test revealed significant mass consistency, within the ±5% accepted range. Friability results were markedly lower than the 1.0% ceiling, falling between 0.041% and 0.286%. All tablets met pharmacopeial disintegration threshold (≤15 min), but times varied significantly (1.57–6.30 min) across the formulations. Assay analysis depicted drug contents ranging from 95.91% to 97.22% of the 500 mg label aligning the pharmacopeial limit. Impurity analysis further validated product`s integrity, with concentrations of dicyandiamide and other unspecified impurities within the threshold’s limits. In conclusion, all evaluated metformin brands met the pharmacopeial standards for uniformity, potency, disintegration time, and purity. These results confirm their pharmaceutical equivalence and standard quality, accrediting their substitutability for clinical use within an institutional formulary. This research supplies pivotal quality verification of various brands of the marketed metformin tablets, informing the procurement and formulary management decisions in the tertiary care hospitals.